Energy balance assessment of magnetic materials as theoretical hint for formulation of interoperable magnetic-mechanical equation - Akbar, A.R. (Trans Tech Publications Ltd, 2014)
Theoretical review on magnetic energy conception is still crucial since the recent discourse emerged in various conceptual speculations that lead into inconsistency in mathematical expression. The coming study should direct its formula into an interoperable equation which enables a magnetic energy to be observed as a mechanical work. The forthcoming expression of magnetic energy should represent operation of mechanical work definitely, considering the usage of Permanent Magnet (PM) in numerous mechanical devices. This interoperable magnetic-mechanical equation would be formulated from energy balance principle applied in both magnetic boundary and mechanical boundary. The energy balance assessment would clarify the usage of magnetic energy during the action of mechanical work. A computational study would assist this observation to interpret some magnetic parameters such as flux density B, magnetic strength H, magnetic energy Em on a self-engineered device named Frequent Flux Collider which examines PMs to be attracted and repelled frequently. The research objectives are: 1) Presenting the technique for assessing the energy balance in PM; 2) Proposing an interoperable equation for bridging magnetic energy and mechanical work. In conclusion, the assessment has brought a theoretical hint to the development of interoperable magnetic-mechanical formula. Â© (2014) Trans Tech Publications, Switzerland.